Level Of Knowledge Of Futsal Athletes PON Sumut XXI 2024 Against Doping (Clenbuterol) - Rinaldi Aditya; Heny Setyawati; Sulaiman; Taufiq Hidayah (Journal of Physical Education and Sports, 2025)
The purpose of this study was to determine the extent of knowledge of North Sumatra PON XXI 2024 futsal athletes on doping (clenbuterol). There are several reasons an athlete uses doping to achieve an achievement. One of the reasons is because he did not achieve maximum training results. The research method used is descriptive method with data survey technique, with a sample size of 15 people, namely all North Sumatra PON XXI 2024 futsal athletes with total sampling technique. The instrument used in this study was a questionnaire about clenbuterol doping . The results of research on the level of knowledge of North Sumatra PON XXI 2024 futsal athletes against doping (clenbuterol) are as follows: level of knowledge about doping in the “Good” category with a percentage of 75.00%, level of knowledge about the effects of doping in the “Excellent” category with a percentage of 84.67%, attitude towards doping in the “Good” category with a percentage of 77.82%, and level of knowledge about clenbuterol in the “Good” category with a percentage of 73.97%. The overall research results regarding the level of knowledge of North Sumatra PON XXI 2024 futsal athletes against doping (clenbuterol) in the “Good” category, with a percentage of 77.11%.